2022
DOI: 10.1161/circresaha.121.320518
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection Induces Ferroptosis of Sinoatrial Node Pacemaker Cells

Abstract: Background: Increasing evidence suggests that cardiac arrhythmias are frequent clinical features of coronavirus disease 2019 (COVID-19). Sinus node damage may lead to bradycardia. However, it is challenging to explore human sinoatrial node (SAN) pathophysiology due to difficulty in isolating and culturing human SAN cells. Embryonic stem cells (ESCs) can be a source to derive human SAN-like pacemaker cells for disease modeling. Methods: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 51 publications
0
60
0
2
Order By: Relevance
“…Han et al elegantly demonstrated that SARS-CoV-2 can infect the sinoatrial node in hamsters and human embryonic stem cell-derived sinoatrial-like pacemaker cells resulting in sinoatrial node-dysfunction including changes in calcium handling, activated inflammatory pathways, and induced ferroptosis. 68 Although we did not find evidence of localized or diffuse fibrosis on cardiac MRI or evidence of sinus node dysfunction on ambulatory rhythm monitoring or ECG monitoring during CPET (ie sinus pauses, Wenckebach, blocked PACs), sinus node dysfunction could explain chronotropic incompetence.…”
Section: Alternative Possibility: Sars-cov-2 Alters Sinus Node Functionmentioning
confidence: 56%
“…Han et al elegantly demonstrated that SARS-CoV-2 can infect the sinoatrial node in hamsters and human embryonic stem cell-derived sinoatrial-like pacemaker cells resulting in sinoatrial node-dysfunction including changes in calcium handling, activated inflammatory pathways, and induced ferroptosis. 68 Although we did not find evidence of localized or diffuse fibrosis on cardiac MRI or evidence of sinus node dysfunction on ambulatory rhythm monitoring or ECG monitoring during CPET (ie sinus pauses, Wenckebach, blocked PACs), sinus node dysfunction could explain chronotropic incompetence.…”
Section: Alternative Possibility: Sars-cov-2 Alters Sinus Node Functionmentioning
confidence: 56%
“…Primary pacemaker cells in the heart have been shown to develop ferroptosis-associated cardiac dysfunction after infection with SARS-CoV-2 (ref. 221 ). Moreover, a high-throughput chemical screen showed that the tyrosine kinase inhibitor imatinib and the iron-chelating agent deferoxamine can block SARS-CoV-2 infection and associated ferroptosis 221 .…”
Section: Ferroptosis In Cardiovascular Diseasementioning
confidence: 99%
“… 221 ). Moreover, a high-throughput chemical screen showed that the tyrosine kinase inhibitor imatinib and the iron-chelating agent deferoxamine can block SARS-CoV-2 infection and associated ferroptosis 221 .…”
Section: Ferroptosis In Cardiovascular Diseasementioning
confidence: 99%
“…Researchers using a type of pluripotent stem cell (hPSC) called human embryonic stem cells (hESC), have found that SARS-CoV-2 can readily infect pacemaker cells and induce a process known as ferroptosis [ 7 ]. Apoptosis, necrosis, autophagy, and other kinds of cell death are all distinct from ferroptosis, which is an iron-dependent cell death.…”
mentioning
confidence: 99%
“…The researchers examined the impact of chelating agents on the elimination of iron from the circulation and thus prevent the ferroptosis process. The chelating agents deferoxamine and imatinib were shown to prevent SARS-CoV-2-induced ferroptosis in the heart’s pacemaker cells [ 7 ].…”
mentioning
confidence: 99%